Val av material och utformning av sinnesträdgårdar för gravt utvecklingsstörda - Hermansson, Malin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The purpose of this thesis was to determine what materials should be used when creating a stimulating garden for intellectually handicapped people and whether there are materials that are better than others to use in this kind of environment. How the materials preferably can be used and how the environment should be designed to satisfy the need of each individual will also be discussed. Seriously intellectually handicapped people have the same level of intelligence as a normal 0-2 year old child. It is important to point out that these individuals can not be compared to a normal child in other aspects than the level of abstract thinking and perception of reality. As the grown up intellectually handicapped people have remained a lot longer on this stage of intelligence they have got more experience. (Kylén 1981) It is important with a lot of different experiences for the brain to develop normally, which implies the use of many different materials to achieve the best stimulation (Kylén 1981). This means no material can be said to be better than another. One single material alone can not give the intellectually handicapped person enough experience. During the interviews a common sense was that the most appreciated material seems to be water. The probable cause for this is that water has the ability to stimulate multiple senses at the same time. It is also known to give a quick and distinct response to an action, which is very developing according to Ayren (1983). A material that has a clear variation with the seasons seems to be a positive experience that Kylén (1985) states is important to preserve the stimulating environment and prevent it from being impoverished. The interviews did not come up with any significant information about a material that most intellectually handicapped people do not like. Some materials are however not suitable for this kind of environment for other reasons, such as plants with thorns and spikes. There is a risk that the individuals will hurt themselves as that can not estimate for them selves when to let go of the branch or plant. Gravel should also be avoided as the small stones are easy to put in the mouth. One important aspect of the overall design is the accessibility. Many intellectually handicapped people also have other disabilities such as physical handicaps or reduced sight (Røren, Terneby & Winlund 1986). Wheelchairs should easily be able to move around which put demands on the ground surface. The personnel also have to be able to use a lift if the different individuals need to be lifted down to the ground. People with visual disabilities need sharp contrasts and clear targets from sound or feel experiences. Clear targets are something that all intellectually handicapped people needs to find in a well-known environment (Røren, Terneby & Winlund 1986). These should be made of materials that does not change with the seasons and should not be moved from its place. They should preferably also stimulate multiple senses at the same time to more easily be caught by the different senses. The difficult part with the development of this kind of garden is the individual differences the intellectually handicapped people have. Yet, accessibility and availability must not be improved to such extent that the challenges cease to exist. That is a difficult but important balance, which can be made easier by creating an environment with many different areas.